The Influence of Communication and Work Commitment on Employee Performance - Enang Narlan SAP; Puspita Dewi Sekar Wati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
Employee performance is the result of achieving a job which will affect the achievement of company goals. Achieve good employee performance, can be influenced by factors of communication and work commitment. The purpose of this study was to find out how Communication, Work Commitment, and Employee Performance are contained in the Human Capital Management (HCM) Division of PT. Pindad (Persero) Bandung, as well as to find out how much influence Communication on Employee Performance, Work Commitment to Employee Performance, and the influence of Communication and Work Commitment to Employee Performance. This research is a population study which is all employees in the Division of Human Capital Management (HCM) as respondents in the study. The data collection process used a questionnaire distributed to 30 respondents. The research method used is descriptive and verification (Path Analysis) through a quantitative approach. The results of this study stated that communication was in the quite good category, work commitment was in the quite good category and employee performance was in the quite good category. The results of the path analysis calculation show that communication has an effect on employee performance, and work commitment has an effect on employee performance.